Hippophae rhamnoides L. leaf extract diminishes oxidative stress, inflammation and ameliorates bioenergetic activation in full-thickness burn wound healing - Ashok Priyadarshi; Gaurav K. Keshri; Asheesh Gupta (Phytomedicine Plus, 2022)
Background: Globally, burn wounds are the prominent cause of morbidity and occasionally mortality, besides psychological and financial burden to the patients and health care systems. Numerous medical complexities associated with burn injuries prompted the quest for novel, practical therapeutic healing approaches, which could potentially influence different phases of the repair process positively. Purpose: The present study investigates the influence of Seabuckthorn leaf aqueous lyophilized extract (SBTL-ALE) on full-thickness burn wounds in rats to establish its healing efficacy and to explore its possible mechanisms of action concerning molecular, cellular, and histopathological features. Methods: Transdermal burn wound created on the dorsal surface of the rat. Animals were randomly distributed into three different groups and topically treated with vehicle base (control group), 2.5% SBTL-ALE ointment (experimental group) and silver sulfadiazine cream (SSD, positive drug control group) twice daily for seven consecutive postwounding days. Results: Immunohistochemical analyses revealed enhanced proliferation, re-epithelialization, neovascularization, dermal hydration as demonstrated by significantly up-regulated (p < 0.05) expression of PCNA, cytokeratin-14, CD31, and aquaporin3, respectively in SBTL-ALE treated group as compared with the control and SSD groups. Picrosirius red staining confirmed the deposition of well-aligned, densely-packed, mature collagen in the SBTL-ALE group. The signature markers of oxidative stress and inflammation (ROS, 3-nitrotyrosine, NOS-2, NF-κB, TNF-α, IL-1β, IL-6) were found to be significant (p < 0.05) decreased in the treated group as compared to the control. Immunoblot analysis exhibited that SBTL-ALE treatment conferred cytoprotection as evidenced by significantly (p < 0.05) up-regulated expression of GRP78, thermo-sensitive cation channel (TRPV3), and HIF-1α. Additionally, activation of energy metabolism and bioenergetics (increased hexokinase, citrate synthase, G6PD, cytochrome c oxidase, ATP, decreased LDH) was observed after SBTL-ALE treatment. Conclusion: SBTL-ALE treatment confers cytoprotection, redox homeostasis, cellular proliferation, re-epithelialization, angiogenesis, and dermal hydration during repair of full-thickness burn wound healing in rats. Furthermore, its treatment attenuates oxidative stress, inflammatory responses and enhances bioenergetic activation. Taken together, SBTL-ALE topical application augments burn wound healing, which could be of high clinical significance. The leads from the present findings could serve as valuable information for further applications of SBTL-ALE in pharmaceuticals and cosmeceuticals.